2013
DOI: 10.3906/bot-1209-29
|View full text |Cite
|
Sign up to set email alerts
|

A new species of Bellevalia (Hyacinthaceae) from Turkey

Abstract: Bellevalia malatyaensis Uzunh. & H.Duman is described and illustrated as a new species from East Anatolia. The distribution area of this species is restricted to Erkenek (Malatya)-Gölbaşı (Adıyaman). It grows in open areas of Pinus brutia Ten. forest. It resembles Bellevalia gracilis Feinbrun, but differs in scapose habitus, leaves, and characters of the capsule. The morphological diagnostic characters and karyological features are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 11 publications
0
17
0
Order By: Relevance
“…Turkey is one of the richest countries in the world in terms of flora and new Turkish species were added in 2013 and 2014 (Öztürk and Çetin, 2013;Karaman Erkul and Aytaç, 2013a;Koç and Aksoy, 2013;Uzunhisarcıklı et al, 2013;Sağıroğlu and Akgül, 2014). In addition to this, there are revisions of some genera from Turkey (Yıldız and Çırpıcı, 2013;Karaman Erkul and Aytaç, 2013b;Akan and Aytaç, 2014).…”
mentioning
confidence: 99%
“…Turkey is one of the richest countries in the world in terms of flora and new Turkish species were added in 2013 and 2014 (Öztürk and Çetin, 2013;Karaman Erkul and Aytaç, 2013a;Koç and Aksoy, 2013;Uzunhisarcıklı et al, 2013;Sağıroğlu and Akgül, 2014). In addition to this, there are revisions of some genera from Turkey (Yıldız and Çırpıcı, 2013;Karaman Erkul and Aytaç, 2013b;Akan and Aytaç, 2014).…”
mentioning
confidence: 99%
“…Species-differentiating characters used in this study to delimit distinction between species includes flower size, pattern of perigone lobes, pattern of diaphragm, pattern of window, size of aperture, number of processes, ramenta, and number of anthers. The application of flower differences have been widely used to differentiate between species in other groups of flowering plants for example in Magnoliaceae (Chen & Zeng, 2013), Hyacinthaceae (Uzunhisarcıklı et al, 2013), and Orobanchaceae (Zare & Dönmez, 2013 Diagnoses: This species is similar to Rafflesia azlanii by the perigone lobes covered by rows of coalesced white warts. It is different from Rafflesia azlanii by the absence of marginal ring of white warts on the periphery of the window, more rows of coalesced white warts on the perigone lobes, higher number of concentric rings of white warts on the window, larger number and rings of circular dots on the diaphragm, larger number and rings of processes on the upper surface of the disc, and more anthers (see Table).…”
Section: Methodsmentioning
confidence: 99%
“…Some of these new described species are diploids (2n = 2x = 8), such as Bellevalia leucantha K. Persson, 2006, Bellevalia malatyaensis Uzunhisarcikli & Duman, 2013 and Bellevalia koyuncui Karabacak & Yildirim, 2015 (Persson 2006, Uzunhisarcikli et al 2013, Karabacak et al 2015). Polyploid species such as Bellevalia pseudolongipes Karabacak & Yildirim, 2014 (Karabacak et al 2014), Bellevalia clusiana Grisebach, 1844 (Yaylaci et al 2009) and Bellevalia edirnensis N.Özhatay & Mathew, 1991 (Özhatay et al 1991b) were identified as triploid, tetraploid and hexaploid respectively.…”
Section: Introductionmentioning
confidence: 99%